Pelatihan Berwirausaha Sampah dan Manajemen Sampah di Desa Argorejo, Sedayu, Bantul, Yogyakarta - Siti Kurnia Widi Hastuti; Fatwa Tentama; Surahma Asti Mulasari; Triwahyuni Sukesi; Sulistyawati Sulistyawati; Muchsin Maulana (Jurnal Pengabdian Pada Masyarakat, 2020)
ENTREPRENEURSHIP AND WASTE MANAGEMENT TRAINING IN ARGOREJO VILLAGE, SEDAYU, BANTUL, YOGYAKARTA. Ministry of Environment noted that the average population of Indonesia produces around 2.5 liters of waste per day or 625 million liters of the total population. This condition will continue to grow according to the environment. According to the Indonesian Waste Statistics (2012) the amount of waste that appears throughout Indonesia reaches 38.5 million tons per year with the dominant waste being in Java (21.2 million tons per year). Waste generation will not decrease or run out and will even continue to grow along with the growth of human population and the higher and more complex human activities. The accumulation of waste that is getting bigger from day to day will reduce space and disrupt human activities so that the human goal to improve the quality of life actually makes the quality of life decrease due to waste generation problems.Method used is to provide counseling and training directly to the general public with material for entrepreneurship motivation and waste bank management using lecture, discussion, and question and answer methods. Results obtained were the extension activities and the training went well and the participants actively participated in the extension activities to completion. Counseling is done interactively between the speakers and the participants present.